Luminescence chronology for identifying depositional sequences in an uplifted coast since the Middle Pleistocene, eastern Japan - Tamura, T.; Okazaki, H.; Naya, T.; Nakashima, R.; Nakazato, H.; Seike, K.; Okuno, J. (Frontiers in Earth Science, 2022)
Application of feldspar post-infrared infrared stimulated luminescence (pIRIR) dating is an advantageous trapped charge dating method that potentially improves our understanding of long-term sea-level changes and regional tectonics. The Kanto coastal plain, eastern Japan is situated in a unique tectonic setting near the triple junction of plate boundaries and characterized by extensive development of the Last Interglacial raised marine terrace in contrast to the longer-term subsidence trend. In this paper we document the application of feldspar pIRIR dating to a 35-m-long sediment core collected from the marine terrace in the northeastern Kanto plain and examine how effective its chronology is for identifying depositional sequences related to the relative sea-level fluctuations since the Middle Pleistocene. The sediment core shows a succession of seven facies units, A to G, in ascending order, representing shallow marine to shelf (units A to C), fluvial to brackish salt marsh (unit D), beach to shoreface (unit E), fluvial to aeolian (unit F), and loess (unit G) sedimentation. According to pretests, pIRIR at 225 ºC after prior infrared stimulated luminescence (IRSL) at 50 ºC (pIRIR225) was chosen as an optimal signal for dating. pIRIR225 is characterized by modest anomalous fading with an average g2days-value 1.8 %/decade. Fading-corrected pIRIR225 ages are consistent with the stratigraphy. Units A and B are dated as Marine Oxygen Isotope Stage (MIS) 7 and units C to F as MIS 5. However, uncertainties of individual age estimates do not allow further chronological correlation. Instead, using sea-level changes inferred from characteristic facies transitions as additional constraints, units C to F can be correlated to substages in MIS 5. Unit E represents coastal progradation during the MIS 5c sea-level highstand, which refines the date of the marine terrace around the core site as MIS 5c and revises up the rate of tectonic uplift accordingly. Our results exemplify a successful application of feldspar pIRIR dating for identifying depositional sequences formed in relations to 100-kyr glacial cycles, in which with additional information of the sedimentary facies higher-frequency sequences may be defined.